2015
DOI: 10.1128/jcm.02059-14
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Susceptibility Testing of Mycobacterium tuberculosis Isolates for Amikacin and Kanamycin Resistance by Use of a Rapid Sloppy Molecular Beacon-Based Assay Identifies More Cases of Low-Level Drug Resistance than Phenotypic Lowenstein-Jensen Testing

Abstract: eResistance to amikacin (AMK) and kanamycin (KAN) in clinical Mycobacterium tuberculosis strains is largely determined by specific mutations in the rrs gene and eis gene promoter. We developed a rapid, multiplexed sloppy molecular beacon (SMB) assay to identify these mutations and then evaluated assay performance on 603 clinical M. tuberculosis DNA samples collected in South Korea. Assay performance was compared to gold-standard phenotypic drug susceptibility tests, including LowensteinJensen (LJ) absolute con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…The long probe length of the SMB probes and their mismatch tolerance capacity allowed us to design probes with programmable hybridization kinetics that could identify a wide range of mutations using a relatively small number of probes (34,42,53,54). Our analytic studies demonstrated robust and reproducible T m peaks that permitted error-free differentiation between wild-type and mutant target sequences, even at limiting concentrations of the target sequence.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The long probe length of the SMB probes and their mismatch tolerance capacity allowed us to design probes with programmable hybridization kinetics that could identify a wide range of mutations using a relatively small number of probes (34,42,53,54). Our analytic studies demonstrated robust and reproducible T m peaks that permitted error-free differentiation between wild-type and mutant target sequences, even at limiting concentrations of the target sequence.…”
Section: Discussionmentioning
confidence: 94%
“…There is increasing evidence that different resistance mutations may be associated with different MICs and may confer variable susceptibilities to different drugs within a given drug category (34,35,(44)(45)(46). We investigated whether the T m generated by each SMB could be used to specifically identify individual mutations (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations